A population of short-period variable quasars from PTF as supermassive black hole binary candidates. Issue 2 (28th July 2016) - Charisi, M.; Bartos, I.; Haiman, Z.; Price-Whelan, A. M.; Graham, M. J.; Bellm, E. C.; Laher, R. R.; Márka, S.
Abstract: Supermassive black hole binaries (SMBHBs) at sub-parsec separations should be common in galactic nuclei, as a result of frequent galaxy mergers. Hydrodynamical simulations of circum-binary discs predict strong periodic modulation of the mass accretion rate on time-scales comparable to the orbital period of the binary. As a result, SMBHBs may be recognized by the periodic modulation of their brightness. We conducted a statistical search for periodic variability in a sample of 35 383 spectroscopically confirmed quasars in the photometric data base of the Palomar Transient Factory (PTF). We analysed Lomb–Scargle periodograms and assessed the significance of our findings by modelling each individual quasar's variability as a damped random walk (DRW). We identified 50 quasars with significant periodicity beyond the DRW model, typically with short periods of a few hundred days. We find 33 of these to remain significant after a re-analysis of their periodograms including additional optical data from the intermediate-PTF and the Catalina Real-Time Transient Survey. Assuming that the observed periods correspond to the redshifted orbital periods of SMBHBs, we conclude that our findings are consistent with a population of unequal-mass SMBHBs, with a typical mass ratio as low as q ≡ M 2 / M 1 ≈ 0.01.